The Adherence Level of Mother who had a Toddler to Carry Out Duty Utilizing the MCH Book in Rembang Village, Blitar - Sunarti Sunarti; Mamik Mamik (Alliance oh Health Activists (AloHA), 2019)
In Rembang Village, Blitar City, there were mother toddlers who did not carry out orders utilizing MCH book, it would affect towards visit toddler services. Mother duty is reading, bringing, keeping and asking to health workers about the contents of a MCH book. The purpose of this research was to know about the adherence level of mother who had a toddler to carry out duty utilizing the MCH book. This research was the descriptive study. The subjects were 52 mothers of toddlers in Rembang Village, selected using quota sampling technique. Data were collected using questionnaires (Morisky Medication Adherence Scale /MMAS with modification). All data obtained is categorical data so that it is analyzed descriptively in the form of frequencies followed by percentages. The 21.2% rate was low adherence, 28.8% was medium and 50% was high. Suggestions for this research is providing socialization about MCH book and give chance mother to ask when there is toddlers integrated service. Keywords: Adherence, Mothers, Toddler, Duty, MCH book